Increasing Wnt signaling in the bone marrow microenvironment inhibits the development of myeloma bone disease and reduces tumor burden in bone in vivo. - Edwards, C; Edwards, J; Lwin, S; Esparza, J; Oyajobi, B; McCluskey, B; Munoz, S; Grubbs, B; Mundy, G (2008)
There is increasing evidence to suggest that the Wnt signaling pathway plays a critical role in the pathogenesis of myeloma bone disease. In the present study, we determined whether increasing Wnt signaling within the bone marrow microenvironment in myeloma counteracts development of osteolytic bone disease. C57BL/KaLwRij mice were inoculated intravenously with murine 5TGM1 myeloma cells, resulting in tumor growth in bone and development of myeloma bone disease. Lithium chloride (LiCl) treatment activated Wnt signaling in osteoblasts, inhibited myeloma bone disease, and decreased tumor burden in bone, but increased tumor growth when 5TGM1 cells were inoculated subcutaneously. Abrogation of beta-catenin activity and disruption of Wnt signaling in 5TGM1 cells by stable overexpression of a dominant-negative TCF4 prevented the LiCl-induced increase in subcutaneous growth but had no effect on LiCl-induced reduction in tumor burden within bone or on osteolysis in myeloma-bearing mice. Together, these data highlight the importance of the local microenvironment in the effect of Wnt signaling on the development of myeloma bone disease and demonstrate that, despite a direct effect to increase tumor growth at extraosseous sites, increasing Wnt signaling in the bone marrow microenvironment can prevent the development of myeloma bone disease and inhibit myeloma growth within bone in vivo.